2019
DOI: 10.14808/sci.plena.2019.018001
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometrics of wing venation to differentiates new species of Scaura Schwarz populations (Hymenoptera: Apidae: Meliponini)

Abstract: Scaura Schwarz, 1938 is a small Neotropical genus of stingless bees widely distributed in Brazil. The new species of Scaura is a widespread species, and its wide distribution may suggest that it is a species complex. In order to differentiate populations that could compose cryptic species, we studied the wing venation variation using geometric morphometrics in 56 workers, 23 of these from remaining of Atlantic Forest in Ceará state and 33 from the Amazon region. Bees from Atlantic Forest differed of the bees f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In the case of the species Scaura cearensis, it was found only in the Meruoca mountain range, a formation with an altitude of 700 -900 meters and characteristics of wet forest, surrounded by the Sertaneja Depression lowlands (Caatinga Vegetation on Crystalline Relief) on all sides, that may have acted as a natural barrier causing the geographic isolation of this group of bees of the genus Scaura, which for a long time under the environmental characteristics of this region allowed for speciation (Nogueira et al 2019b). Residual massifs such as those of the Meruoca and the Baturité mountain ranges originated from orogenic and erosion processes can function as refuges and also allow the emergence of new animal species (Mantovani 2007, Brandão & Freitas 2014.…”
Section: State Of Rio Grande Do Norte (Carvalho and Zanella 2017)mentioning
confidence: 99%
“…In the case of the species Scaura cearensis, it was found only in the Meruoca mountain range, a formation with an altitude of 700 -900 meters and characteristics of wet forest, surrounded by the Sertaneja Depression lowlands (Caatinga Vegetation on Crystalline Relief) on all sides, that may have acted as a natural barrier causing the geographic isolation of this group of bees of the genus Scaura, which for a long time under the environmental characteristics of this region allowed for speciation (Nogueira et al 2019b). Residual massifs such as those of the Meruoca and the Baturité mountain ranges originated from orogenic and erosion processes can function as refuges and also allow the emergence of new animal species (Mantovani 2007, Brandão & Freitas 2014.…”
Section: State Of Rio Grande Do Norte (Carvalho and Zanella 2017)mentioning
confidence: 99%
“…The Atlantic Forest is one of the most diverse Neotropical habitats, harbouring around 7% of the world’s known flora and fauna [ 23 , 24 ]. It hosts more than 20,000 species of plants, about 1,500 species of terrestrial vertebrates, and an undetermined number of invertebrates (mainly arthropods), many undescribed [ 24 – 30 ]. In addition, and in spite of its cycles of connection and disconnection with other Neotropical forests (Andean Forest, Amazonian Forest; [ 31 34 ]), more than 8,000 plants and 550 vertebrates are endemic to the Atlantic Forest, so it hosts almost 5% of all known endemic species [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…From each specimen, the right fore wing was removed, and from the bottom, the microscope slide was mounted with Euparal medium, and photographed (Fig. 1), at the same scale (dos Santos et al, 2009;Nogueira et al, 2019). From each slide 11 anatomical landmarks (Lm), were digitized (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…With this tool, it is possible to discriminate and separate taxonomic groups through the shape, describing the differences using landmark displacements. Several studies have already shown the application of geometric morphometry as an efficient method of differentiation between closely related bee taxa (Combey et al, 2013;Vijayakumar and Jayaraj, 2013;Rattanawannee et al, 2015;Nogueira et al, 2019;dos Santos et al, 2009a;dos Santos et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%